Design and Development of an Augmented Reality Based Storytelling Platform for Interactive Solar System Learning in Primary Education - I Putu Andika Subagya Putra; Ni Wayan Sri Darmayanti; Putu Beny Pradnyana; Luh Made Dwi Wedayanthi (JUITA: Jurnal Informatika, 2026)
Concepts in primary science education, such as the Solar System, are often difficult for students to understand when presented through conventional two-dimensional learning media. This study aims to design and develop a storytelling-driven Augmented Reality (AR) learning platform to support interactive Solar System learning in primary education. A Research and Development (R&D) approach was employed, encompassing needs analysis, conceptual design, prototype development, limited trials, and formative evaluation. The developed platform enables learners to visualize three-dimensional planetary models using marker-based AR accompanied by age-appropriate narrative explanations. Limited trials involving ten fourth-grade students and two science teachers were conducted to examine usability and user perceptions. The findings indicate that students and teachers perceived the platform as engaging and supportive for visualizing abstract astronomical concepts. The novelty of this study lies in the integration of structured storytelling with AR visualization tailored for primary learners within an R&D framework. However, the results are based on formative evaluation and user perceptions; therefore, further studies with larger samples and objective learning outcome measures are recommended.